Extranodal lymphomas at Lima - Chang, Alfonso (2001)
OBJECTIVE: To assess the incidence, clinical–pathological and immunophenotypical characteristics of extranodal lymphomas (ENL) at Lima. MATERIAL AND METHODS: All cases with pathologic diagnosis of ENL done in 1998 in the Institute of Cancer, Social Security and Army general hospitals were studied. Data was obtained from medical records. Samples were reviewed by two pathologist using the REAL classification. RESULTS: 616 non-Hodgkin’s lymphomas (308 of them were extranodal), and 88 Hodgkin’s lymphomas were diagnosed. ENLs were predominantly gastric (70 cases), and cutaneous (49 cases). Mainly, lymphomas of the stomach, Waldeyer’s ring, intestine, and salivary glands showed B trait, and lymphomas of the skin an nasal pharynx showed T trait. The marginal zone MALT lymphomas were the commonest in the digestive tract. CONCLUSION: The higher frequency of ENL in the gastrointestinal tract, skin and oral pharynx agreed with previous studies in other regions. There were more ENLs than expected, as compared with nodal lymphomas.